Life-cycle assessment of hydrogen production via catalytic gasification of wheat straw in the presence of straw derived biochar catalyst - Loy, A.C.M. (Elsevier Ltd, 2021)
The environmental footprints of H2production via catalytic gasification of wheat straw using straw-derived biochar catalysts were examined. The functional unit of 1 kg of H2was adopted in the system boundaries, which includes 5 processes namely biomass collection and pre-treatment units (P1), biochar catalyst preparation using fast pyrolysis unit (P2), two-stage pyrolysis-gasification unit (P3), products separation unit (P4), and H2distribution to downstream plants (P5). Based on the life-cycle assessment, the hot spots in this process were identified, the sequence was as follows: P4 > P2 > P1 > P3 > P5. The end-point impacts score for the process was found to be 93.4017 mPt. From benchmarking analysis, the proposed straw-derived biochar catalyst was capable of offering almost similar catalytic performance with other metal-based catalysts with a lower environmental impact. Â© 2021 Elsevier Ltd